The Algerian revolution in Maghreb magazines- Dawate al hak Magazine as a model - Sidi Mohamed, amara (The Algerian Historical Journal, 2026)
The The Algerian issue and its triumphant revolution in the 1950s constituted the first title among the lines of writers and poets across the world, especially the brotherly Arab countries, because the issue of Algeria’s independence was rightly representing the struggle of the free people to regain the usurped right from the aggressor occupier, smash his false ego, and break the myth of his military greatness. The forms of support varied between nodal rooting, organized military strikes, and organizing ranks, to culminate in the establishment of the Interim Government, and expanding the circle to the corridors of the United Nations and Friends of Peace. This is what was covered by the magazine: "Da`wah al-Haqq".